Asymmetric Effects of Economic Activityon Inflation : Evidence and Policy Implications - Laxton, Douglas; Meredith, Guy.; Rose, David (Washington, D.C. : International Monetary Fund, 1994)
This paper examines the evidence on asymmetries in the effects of activity on inflation. Data for the G-7 countries are found to strongly support the view that the inflation-activity relationship is nonlinear, with high levels of activity raising inflation by more than low levels decrease it. In the face of such asymmetries, the average level of output in an economy subject to demand shocks will be below the level of output at which there is no tendency for inflation to rise or fall, contrary to the implications of linear models. One implication of these results is that policymakers can raise the average level of output over time by responding promptly to demand shocks, thus reducing the variance of output around trend.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet